2019
DOI: 10.1136/ijgc-2019-000626
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of ovarian reserve and reproductive outcomes inBRCA1orBRCA2mutation carriers

Abstract: IntroductionThe clinical impact on fertility in carriers of BRCA1 and BRCA2 mutations remains unclear. The aim of this study was to assess ovarian reserve as measured by anti-mullerian hormone levels in BRCA1 or BRCA2 mutation carriers, as well as to investigate the impact of anti-mullerian hormone levels on reproductive outcomes.MethodsThe study involved a cohort of women who tested positive for BRCA1 and BRCA2 screening or were tested for a BRCA1 or BRCA2 family mutation. Blood samples were collected for ant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 24 publications
1
10
0
Order By: Relevance
“…One study apparently fulfilling inclusion criteria, categorized women as low risk due to a negative family history for breast and/or ovarian cancer, without a confirmation BRCA test, therefore it was excluded [ 23 ]. At the end of the screening, ten studies resulted eligible and were included in the meta-analysis [ 5 , 6 , 10 , [24] , [25] , [26] , [27] , [28] , [29] , [30] ]. The group populations of the ten selected studies, considered as upper limit 40 [ [24] , [25] , [26] ], 42 [ 6 ], and 45 years old [ 5 , [27] , [28] , [29] , [30] ].…”
Section: Resultsmentioning
confidence: 99%
“…One study apparently fulfilling inclusion criteria, categorized women as low risk due to a negative family history for breast and/or ovarian cancer, without a confirmation BRCA test, therefore it was excluded [ 23 ]. At the end of the screening, ten studies resulted eligible and were included in the meta-analysis [ 5 , 6 , 10 , [24] , [25] , [26] , [27] , [28] , [29] , [30] ]. The group populations of the ten selected studies, considered as upper limit 40 [ [24] , [25] , [26] ], 42 [ 6 ], and 45 years old [ 5 , [27] , [28] , [29] , [30] ].…”
Section: Resultsmentioning
confidence: 99%
“…A major concern among BRCA1/2 pathogenic variant carriers is the potential higher risk of premature ovarian insufficiency (POI) [22,23]. Most of the available preclinical evidence suggests that BRCA mutations could directly accelerate ovarian aging, reducing the ovarian reserve both quantitatively and qualitatively [24][25][26][27][28][29]. BRCA1 and 2 are known to be involved in DNA repair mechanism, through ATM-mediated regulation of the DNA double-strand breaks (DSBs) repair [23,30].…”
Section: Main Textmentioning
confidence: 99%
“…Levels of anti-Müllerian hormone (AMH) are considered a quantitative marker of ovarian reserve, although not predictive of chances of spontaneous pregnancy [37]. In some studies, the levels of AMH were found to be significantly lower in women carrying pathogenic variants in BRCA1 [24][25][26]30] or BRCA2 [27,29] or both genes [28], while other studies reported no significant difference with controls [36,38]. Clinical studies describing a decreased oocyte quality in human carriers of BRCA pathogenic variants (i.e., an increase in aneuploidies) are still lacking, while age at natural menopause among BRCA carriers is difficult to ascertain, because of various types of selection bias, diverse control groups, and the small population of the studies [39][40][41][42].…”
Section: Main Textmentioning
confidence: 99%
“…In our search, 11 articles [17][18][19][20][21][22][23][24][25][26][27] considered anti-Mullerian hormone and antral follicular count as indexes of ovarian function in BRCA mutation carriers compared with wild-type controls (Table 1). In fact, anti-Müllerian hormone levels and antral follicular count are considered predictors of ovarian response during in vitro fertilization techniques, with lower levels suggestive of a poor response.…”
Section: Reviewmentioning
confidence: 99%
“…Several studies have validated anti-Müllerian hormone as a direct biomarker for ovarian aging, which reflects the decline in reproductive capacity. 29 30 In our search, we considered 11 studies [17][18][19][20][21][22][23][24][25][26][27] evaluating anti-Müllerian hormone levels as an index of the ovarian reserve, comparing BRCA carriers with wild-type controls. Four studies concluded that BRCA mutation carriers had lower levels of anti-Müllerian hormone compared with BRCA wild-type patients 17 20 22 23 while five studies had the opposite results, reporting BRCA patients who had higher anti-Müllerian hormone levels compared with BRCA wild-type patients.…”
Section: Anti-müllerian Hormonementioning
confidence: 99%